Amphiphilic Cyclic Peptoids That Exhibit Antimicrobial Activity by Disrupting Staphylococcus aureus Membranes. Issue 17 (19th April 2013) - Huang, Mia L.; Benson, Meredith A.; Shin, Sung Bin Y.; Torres, Victor J.; Kirshenbaum, Kent
Abstract: There is a significant unmet need for new antimicrobial agents that can address antimicrobial resistance. One promising group of antimicrobials is the antimicrobial peptides (AMPs) and their synthetic mimics. In particular, synthetic sequence‐specific oligomers of N ‐substituted glycine, termed "peptoids", have been found to show potent antimicrobial activity against bacterial pathogens in vitro and can act against the emergence of antimicrobial resistance. In this study, we evaluate the antimicrobial activity of cyclic peptoid oligomers against clinical isolates of methicillin‐resistant Staphylococcus aureus (MRSA). The presence of the macrocyclic constraints can enforce a globally amphiphilic organization of the peptoid side‐chains. Several of these new amphiphilic compounds show potent and selective antimicrobial activity. Electron microscopy experiments demonstrate that the peptoids target and damage the MRSA cytoplasmic membrane through the formation of pores. These results substantiate the potential of peptoids as antimicrobial therapeutic agents for the treatment of S. aureus infections. Abstract : Macrocyclic peptoid oligomers that organize into globally amphiphilic faces show potent antimicrobial activity against clinical isolates of methicillin‐resistant Staphylococcus aureus (MRSA) and disrupt the bacterial cell surface, as shown by scanning electron microscopy. Scale bar: 300 nm.